On locally perturbed equilibrium distribution functions - Malyshev, D. V.; Malyshev, P. V. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We construct a new class of locally perturbed equilibrium distribution functions for which local (in time) solutions of the BBGKY equations can be extended onto the entire time axis.